2023
DOI: 10.1002/smll.202208274
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Interface Engineering of Nanostructures for Photoelectrochemical Energy Harvesting Applications

Abstract: With rapid and continuous consumption of nonrenewable energy, solar energy can be utilized to meet the energy requirement and mitigate environmental issues in the future. To attain a sustainable society with an energy mix predominately dependent on solar energy, photoelectrochemical (PEC) device, in which semiconductor nanostructure‐based photocatalysts play important roles, is considered to be one of the most promising candidates to realize the sufficient utilization of solar energy in a low‐cost, green, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 308 publications
0
28
0
Order By: Relevance
“…The overuse of conventional fossil fuels has resulted into a sharp increase in CO 2 concentration in air, causing serious energy crisis and global climate issues. [94,[163][164][165][166] Electrocatalytic CO 2 RR is one of the most promising approaches for the direct conversion of CO 2 into valuable chemical feedstocks and fuels. Because of the high conductivity, unique porous structure, and electron-rich nature of 2D GDY, it has been widely used to engineer the surface of (photo)electrocatalysts for dramatically improved CO 2 reduction efficiency and remarkable selectivity.…”
Section: Co 2 Rrmentioning
confidence: 99%
See 1 more Smart Citation
“…The overuse of conventional fossil fuels has resulted into a sharp increase in CO 2 concentration in air, causing serious energy crisis and global climate issues. [94,[163][164][165][166] Electrocatalytic CO 2 RR is one of the most promising approaches for the direct conversion of CO 2 into valuable chemical feedstocks and fuels. Because of the high conductivity, unique porous structure, and electron-rich nature of 2D GDY, it has been widely used to engineer the surface of (photo)electrocatalysts for dramatically improved CO 2 reduction efficiency and remarkable selectivity.…”
Section: Co 2 Rrmentioning
confidence: 99%
“…PDs are one of the most vital optoelectronic devices that can convert light into electrical signals whether in industrial applications or daily life. [163,[268][269][270][271][272][273][274][275] Inspired by the high electrical conductivity and carrier mobility of GDY, [20,276,277] GDY nanostructure-based PDs, such as GDYO-based PDs, [71] GDY/MoS 2 -based PDs, [278] GDY@MoS 2 /WS 2 -based PDs, [279] TiO 2 :GDY/Mg 0.3 Zn 0.7 O-based PDs, [280] GDY:ZnO-based PDs, [281] and SWCNT/GDY-based PDs, [40] have been rapidly flourished. For example, in 2020, ultrathin GDY NSs were spin-coated onto a clean poly(ethylene terephthalate) (PET) film to fabricate a novel GDY-based photoelectrochemical (PEC)-type PD electrode.…”
Section: Photodetectionmentioning
confidence: 99%
“…The most intuitive external-field-assisted strategy is to apply an external bias on the catalysis in a photoelectrocatalytic system. The recombination of photogenerated hot electrons and holes is effectively inhibited by the directional motion of electrons under the external electric field [250,251] . However, the prerequisite for the immobilization of photocatalysts in the form of an electrode is not always satisfied, such as in powders or films.…”
Section: Improving Hot Carrier Utilization Efficiencymentioning
confidence: 99%
“…Notably, monolayer TMDs can exhibit direct band gap properties and emit bright photoluminescence (PL), positioning them as clear candidates for next-generation optoelectronic devices . It has been demonstrated that morphological and structural arrangements of nanomaterials play crucial roles in their properties, and therefore the performance of devices can be regulated by precisely controlling morphology and structure. Various techniques have been explored to manipulate the excitonic and electronic characteristics of monolayer TMDs, including strain, , layer-dependent engineering, electron doping, , plasma treatment, alterations in dielectric environments, and the application of external electric fields …”
Section: Introductionmentioning
confidence: 99%